Identifying analytics for high throughput bioprocess development studies1. Issue 7 (15th February 2013) - Konstantinidis, Spyridon; Kong, Simyee; Titchener‐Hooker, Nigel
Abstract In recent years, high throughput screening (HTS) studies have been increasingly employed as an integral element of bioprocess development activities. These studies are often limited by an analytical bottleneck; they generate multiple samples for analysis and the available analytical methods cannot always cope with the added analytical burden. A potential solution to this challenge is offered by the deployment of appropriate analytics. This article outlines features of analytical methods that affect their fit to high throughput (HT) applications. These are discussed for a range of analytics frequently used in bioprocess development studies of monoclonal antibodies. It then outlines how these features need to be considered in order to classify analytical methods in terms of their particular application in high throughput scenarios. Biotechnol. Bioeng. 2013; 110: 1924–1935. © 2013 Wiley Periodicals, Inc.